Saturated N-heterocyclic carbene based thiele's hydrocarbon with a tetrafluorophenylene linker - Kundu, Gargi; De, Sriman; Tothadi, Srinu; Das, Abhishek; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2019)
The synthesis of a SIPr [1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] derived Kekule diradicaloid with a tetrafluorophenylene spacer (3) has been described. Two synthetic routes have been reported to access 3. The cleavage of C-F bond of C6F6 by SIPr in the presence of BF3 led to double C-F activated compound with two tetrafluoro borate counter anions (2), which upon reduction by lithium metal afforded 3. Alternatively, 3 can be directly accessed in one step by reacting SIPr with C6F6 in presence of Mg metal. Compounds 2 and 3 were well characterized spectroscopically and by single-crystal X-ray diffraction studies. Experimental and computational studies support the cumulenic closed-shell singlet state of 3 with a singlet-triplet energy gap (Delta ES-T) of 23.7 kcal mol(-1).
Keywords: C-F activation; Density functional calculations; fluorine; Kekule diradicaloids; saturated NHC